Stress, Anxiety, and Depression Symptoms in a Population Sample in The Initial Stage of The Coronavirus (COVID-19) Pandemic Outbreak - Samah R. I Elrefaey (Evidence-Based Nursing Research)
Context: Changes in everyday life have been rapid and drastic, with the virus surge outbreaks, the death rate escalating, and stringent steps to control the disease spread increasing across regions of the world. While significant attention has been paid to efforts to diagnose people with the coronavirus infection, recognizing the mental health needs of people affected by this pandemic has been ignored relatively. The psychological impact of the Coronavirus Disease 2019 (COVID-19) outbreak and lockdown measures on the Egyptian population are unknown.